How Good Policies and Business Ethics Enhance Good Quality of Life : The Selected Works of Alex C. Michalos - Michalos, Alex C. (Springer International Publishing : Imprint: Springer, 2017)
This volume provides bridges from the social sciences to business ethics and from the latter to the quality of life, by connecting the research themes of quality of life, social sciences, including public policy-making, and business ethics or corporate responsibility. It builds on the premise that public policy making is essentially a species of good decision making, as explained in the first volume. It shows that, because most developed countries function as market economies whose governments depend on taxation to pay for their services and because a large proportion of government revenue comes from well-regulated, responsible corporations, the quality of people's lives is highly dependent upon good public policies, taxation and business ethics. The volume presents and examines ethical/moral problems arising in market economies since the first century BCE, including the first appearance of the business case for business ethics, fourteen arguments concerning the neglect of business ethics, business ethics issues for the 1990s and beyond, the loyal agent's argument, advertising, the importance of trust, public opinion polling, public program evaluation, and a critique of the relatively new monster of super-capitalism. In addition, it deals with connections among the concepts of efficiency, morality, and rationality related to decision making in general and public policy making in particular. Finally, it explains relationships between outcomes measurement and performance indicators in general and performance-based management in public administration, the taxation of net wealth and financial transactions.
Keywords: Social sciences.; Business ethics.; Social responsibility of business.; Public policy.; Medical research.; Quality of life.; elektronické knihy; electronic books